2002
DOI: 10.1021/jp0138936
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Double Nuclear Magnetic Resonance Study of the Local Structure of Calcium Phosphate Nanoparticles Synthesized by a Wet-Mechanochemical Reaction

Abstract: Calcium phosphate synthesized by a wet-mechanochemical reaction between Ca(OH) 2 and H 3 PO 4 is identified by X-ray diffractometry as an apparently single phase of hydroxyapatite (HAp). We examined more detail on the local structure of the product by high-resolution 1 H and 31 P solid-state double nuclear magnetic resonance (NMR) spectroscopy. Adsorbed and structural waters, as well as two kinds of OH groups in HAp, were observed in the inversion recovery 1 H magic angle spinning (MAS) spectra. HAp and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 19 publications
9
86
0
1
Order By: Relevance
“…Only one asymmetric peak is observed. Its maximum is slightly shifted compared to non-substituted HA (2.6 ppm vs 2.8 ppm), [80] and the signal is ~1 ppm broader at half maximum, with a tailing towards high frequencies. These observations show that there is a larger variety of environments around the phosphates in Mg-HA, which can be due to the presence of Mg 2+ cations occupying different neighbouring positions (see Figure 2), and also to the structural distortions of the HA lattice which can induce slight rotations of the phosphate groups and small variations in the P-O bond distances and O-P-O bond angles.…”
Section: Dft Calculations Of the Nmr Parametersmentioning
confidence: 89%
“…Only one asymmetric peak is observed. Its maximum is slightly shifted compared to non-substituted HA (2.6 ppm vs 2.8 ppm), [80] and the signal is ~1 ppm broader at half maximum, with a tailing towards high frequencies. These observations show that there is a larger variety of environments around the phosphates in Mg-HA, which can be due to the presence of Mg 2+ cations occupying different neighbouring positions (see Figure 2), and also to the structural distortions of the HA lattice which can induce slight rotations of the phosphate groups and small variations in the P-O bond distances and O-P-O bond angles.…”
Section: Dft Calculations Of the Nmr Parametersmentioning
confidence: 89%
“…In this respect, the possibility to turn quite smoothly the bulk structure from highly to poorly crystalline or actually disordered by changing preparation conditions, such as temperature, presence of anionic and/or cationic substituents, nucleation on collagen fibers, is well known [101]. Still, in recent years, several studies [102][103][104][105] revealed that HA nanoparticles can be coated by an amorphous, non-apatitic surface layer surrounding a crystalline hydroxyapatite bulk. However, the possibility of obtaining apatitic particles with crystalline structure extended up to the surface was recently reported [106].…”
Section: The Inorganic Bone Matrix: Hydroxyapatitementioning
confidence: 99%
“…At about 190°C and 340°C, there are small and big peaks in the first derivative curve of the apatite obtained by calcination, these peaks accompanying weight losses of 0.4 and 0.9%, respectively. These losses might refer to the dehydration of ions HPO 4 − 2 according to the following reaction [44]:…”
Section: Thermal Gravimetric Analysismentioning
confidence: 99%
“…Therefore, different production methods were reported such as mechanochemistry [3,4], ultrasonic irradiation [5], microwave irradiation [6,7], sol-gel [8][9][10][11], chemical precipitation [12,13], hydrothermal method [14][15][16], hydrolysis [17], microemulsion [18][19][20], and emulsion liquid membrane [21]. The synthesized HAp does not have adequate biological properties as the natural apatite existing in bones.…”
Section: Introductionmentioning
confidence: 99%